Firefly encyclopedia of reptiles and amphibians - Mattison, Christopher (Richmond Hill, Ont. : Firefly Books, 2008)
A comprehensive encyclopedia, illustrated with full color drawings and photographs, on the biology and behavior of all reptiles and amphibians. Designed for quick retrieval of basic facts, there are also specially commissioned articles by experts.
Amphibians : Caecilians -- Salamanders and newts -- Frogs and toads -- Reptiles : Turtles and tortoises -- Lizards -- Worm lizards -- Snakes -- Tuatara -- Crocodilians.
Includes index.
Includes bibliographical references : (pages 229-231) and index.
Keywords: Reptiles -- Encyclopedias; Amphibians -- Encyclopedias